Stagnant growth and income class structure in European countries - Pérez-Moreno, Salvador Jesús; Bárcena-Martín, Elena María (My University, 2019)
In recent years, there has been increasing debate about the low economic growth and the risk of secular stagnation in economically advanced countries. Some authors point out possible links between secular stagnation and income inequality, causally in both directions. Taking as a reference point the theoretical literature on the relationship between economic growth and income distribution, this study examines the extent to which different levels of economic growth are associated with the income class structure in European countries between 1993 and 2016, focusing on income distribution before taxes and transfers (market incomes). We highlight that in recession periods the size and income share of the middle class decrease, while the opposite occurs in periods with strong economic growth rates. Nevertheless, when growth rates are modest the patterns are much less clearly defined. Some policy and institutional implications are discussed in order to tackle the concerns of secular stagnation and inequality simultaneously.
Keywords: Crecimiento económico; Desigualdad económica; Ingresos; Secular stagnation; Economic growth; Income inequality; Income class structure